PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER DAPAT MENINGKATKAN PRESTASI SD NEGERI 011 TANDUN - Sri Sumartiatun (JURNAL PENDIDIKAN ROKANIA, 2020)
The values ​​of character education is a culture that has been attached to a community group. The values ​​of character education ​​are part of the wealth and assets that need to be preserved. A society can be recognized by its identity by knowing and knowing the value of the characters they have. The value of character education implanted in State Elementary School 011 Tandun is the value of religious character education, toughness, caring and cultural values ​​of the nature of human relationships with human beings. So that the character education value to be maintained sustainability, it is necessary to plant the values ​​of the characters through various activities done by the school. This research is qualitative research by using descriptive method of analysis. The object of this study is the value of character education and data sources obtained from school personnel and students. The data of this research are all data of character education values ​​conducted in various school activities. The result of the research is the improvement of school achievement as an implication of the implantation of character education values ​​as follows: (1) the cultural value of the nature of the relationship between human beings and others, (2) the values ​​of religious education, (3) values ​​of educational toughness, (4) values ​​of caring education. These four cultural and educational values ​​can be implicated in formal education in schools.